Factors Affecting Capsular Volume Changes and Association With Outcomes After Bankart Repair and Capsular Shift - Park, Jin-Young; Chung, Seok Won; Kumar, Gurudeo; Oh, Kyung-Soo; Choi, Jin Hyeok; Lee, Deukhee; Park, Sehyung (SAGE PUBLICATIONS INC, 2015)
Background: Capsular laxity is a main contributing factor in recurrent shoulder instability and is suggested to be correlated with increased capsular volume. Arthroscopic capsular shift combined with Bankart repair can reduce the capsular volume and reinforce the redundant capsule; however, as the capsuloligamentous structure has viscoelastic properties, it is possible for the shifted and tensioned capsule of the glenohumeral joint to slowly stretch out again over time, resulting in an increase in capsular volume. Purpose: To analyze changes in capsular volume of the glenohumeral joint over time after arthroscopic Bankart repair and capsular shift, the factors associated with these changes, and their relevance to outcomes. Study Design: Case series; Level of evidence, 4. Methods: Included in this study were 105 patients (mean age, 25.8 +/- 8.2 years) who underwent arthroscopic Bankart repair and capsular shift for anterior shoulder instability and computed tomography arthrography (CTA) at 3 months and 1 year postoperatively and whose various functional outcomes were evaluated preoperatively and at the last follow-up (>12 months). Among these patients, 27 also had preoperative CTA. These 27 patients were used to make comparisons between preoperative and 3-month postoperative CTA measurements, and all 105 patients were used for all other comparisons. Two raters measured the separate anterior and posterior capsular volume and cross-sectional area at the 5-o'clock position using 3-dimensional (3D) Slicer software. These measurements were subsequently adjusted for each glenoid size. The changes in capsular volume and cross-sectional area at the 5-o'clock position over time, the factors related to higher change in anterior capsular volume, and their correlation with outcomes were evaluated. Results: Three months postoperatively, the total and anterior capsular volume and anterior cross-sectional area significantly decreased; however, these values increased again at 1 year postoperatively (all P < .01). The inter-and intraobserver reliabilities of the measurements were excellent (interclass correlation coefficient = 0.717-0.945). Female sex, being an elite athlete, and more dislocations before surgery were related to a higher increase in anterior capsular volume at 1 year (all P < .05). Eight patients had redislocation, and 18 exhibited positive apprehension test postoperatively, and these patients showed significantly higher increases in anterior and total capsular volume at 1 year than did those without redislocation or positive apprehension sign (all P < .01). However, with the exception of Rowe score, a higher increase in anterior capsular volume was not related to functional outcome measures. Conclusion: Surgeons should be aware of the re-increase in anterior capsular volume or restretching trait of the anterior capsule over time, even after successful arthroscopic Bankart repair and capsular shift. In this study, women, elite athletes, and those with frequent dislocations were at high risk of capsular restretching. An increase in capsular volume was related to redislocation and positive apprehension sign as well as with Rowe score.
Keywords: RECURRENT ANTERIOR DISLOCATION; BIOMECHANICAL EVALUATION; SHOULDER INSTABILITY; 3D SLICER; BONE LOSS; REDUCTION; LAXITY; RECONSTRUCTION; CAPSULORRHAPHY; STABILIZATION